Enhancement of Both Intracellular Uptake and Antitumor Action of Cisplatinum on Human Neuroblastoma Cells by Encapsulation in Liposomes - Kamio, Yoshiro (Jpn J Cancer Res, 1989)
Phospholipid vesicles (phosphatidylcholine: phosphatidylserine: cholesterol=6:2:3 in molar ratio) with a small unilamellar structure were used as drug carriers for introducing cis‐diamminedichloroplatinum (CDDP) into human neuroblastoma cells, IMR‐32, GOTO, Nagai, and TGW. DNA synthesis of IMR‐32 cells among the human neuroblastoma cell lines was inhibited most strongly by CDDP‐liposomes. CDDP‐liposomes dose‐dependently inhibited the DNA synthesis of IMR‐32 in a similar fashion to that observed with free CDDP, but the drug concentration required to induce 50% inhibition of DNA synthesis for CDDP‐liposomes (IC50: 0.7 μg CDDP/ml) was 1/3 of the IC50 for free CDDP (2.0 μg CDDP/ml). In support of the marked growth‐inhibitory action of CDDP‐liposomes, the intracellular incorporation rate of CDDP‐liposomes was 3‐fold higher when liposomes were used as carriers than when free CDDP was directly applied. CDDP‐liposomes showed a stronger growth inhibition on IMR‐32 cells at a high cell density than at a low density in culture. CDDP‐liposomes were rapidly incorporated by IMR‐32 cells within 5 min, resulting in the inhibition of DNA synthesis to 40% of the control. Swiss albino mouse 3T3 cells were less inhibited by CDDP‐liposomes than by free CDDP, suggesting that encapsulation of CDDP in liposomes decreases cytotoxicity to normal cells.